The function of T cells in immune thrombocytopenia - Bu, Siyuan; Liu, Min; Yang, Lu; Lee, Pamela; Miller, Heather; Park, Chan-Sik; Byazrova, Maria; Filatov, Alexander; Benlagha, Kamel; Gaber, Timo; Buttgereit, Frank; Gong, Quan; et al. (Frontiers in Immunology, 2025)
Immune thrombocytopenia (ITP) is an autoimmune disease, characterized by increased bleeding due to a reduced platelet count. The pathogenesis of ITP is very complex and involves autoantibody production and T-cell-mediated immune abnormalities. An imbalance of effector and regulatory CD4+ T cells and the breach of tolerance primarily cause ITP, leading to the dysfunctional development of autoreactive Th cells (including Th1, Th2, and Th17 cells) and Tregs. The loss of auto-platelet antigen tolerance in ITP results in autoantibody- and cytotoxic T-cell-mediated platelet clearance. T-cell-related genetic risk factors significantly influence the development and progression of this disease. New therapies targeting T cells have emerged as potentially effective cures for this disease. This review summarizes the role of T cells in ITP.